2015
DOI: 10.1590/0103-8478cr20140293
|View full text |Cite
|
Sign up to set email alerts
|

Ácidos graxos e colesterol da carne de cordeiros confinados recebendo dietas contendo fontes lipídicas e submetidos à restrição e realimentação

Abstract: RESUMO Foram avaliados os efeitos da inclusão de grãos de girassol ou gordura protegida na dieta e da restrição e realimentação sobre a área de olho de lombo, espessura de gordura subcutânea, a composição centesimal, o teor de colesterol e a composição em ácidos graxos da gordura intramuscular do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, increased SFT usually accompanies an increase in the slaughter weight of the animal (EIRAS et al, 2014). In this study, it was observed that the carcass weight decreased with increasing restriction, with the decrease in dry matter intake, thus promoting a reduction in SFT (HOMEM JUNIOR et al, 2015).…”
Section: Variablesmentioning
confidence: 56%
“…In addition, increased SFT usually accompanies an increase in the slaughter weight of the animal (EIRAS et al, 2014). In this study, it was observed that the carcass weight decreased with increasing restriction, with the decrease in dry matter intake, thus promoting a reduction in SFT (HOMEM JUNIOR et al, 2015).…”
Section: Variablesmentioning
confidence: 56%
“…Animals fed the cottonseed diets produced similar results than those fed the control diet for DMI in percentage of BW, probability due NDF and ADF digestibility interference (BECK et al, 2019). The difference for DMI (%BW) between the cottonseed diet and the sunflower and soybean diets seems to be related to cotton linters, resulting in lower NDF digestibility in the cottonseed diet (PIONA et al, 2012), or to their effect in rumen metabolism (PEREIRA et al, 2016;HUMER et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…In intensive animal systems production, oilseeds can increase the energy density of diets (PEREIRA et al, 2016;HUMER et al, 2018). They have enough energy to supply the highest nutritional requirement of fattening animals, reduce time to achieve the slaughter weight, and enhance the nutritional quality of lamb meat (OLIVEIRA et al, 2017;GALLO et al, 2019;VAN LE et al, 2019).…”
Section: Introductionmentioning
confidence: 99%